BRAND EQUITY DEVELOPMENT STRATEGY TO ENHANCE THE COMPETITIVENESS OF FOOD SMALL-MEDIUM ENTERPRISE'S (SMES): CASE STUDIES ON FUDIA-POLINELA AGRI-FOOD CENTRE - Fitriani, Fitriani; Sutarni, Sutarni; Unteawati, Bina; Apriyani, Marlinda; Widyawati, Dewi Kania; Berliana, Dayang (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
The competitiveness of local agri-food needs through various marketing strategies. An essential part of the company's marketing strategy and tactics is recognizing product brand equity in the market. This study aims to identify brand entities, brand communication, and process to build Brand Equity toward local SMEs' competitiveness. A case study approach did at one of the SMEs in Bandar Lampung on the